ELECTROMECHANICAL PRESSURE SENSORS BASED ON GRAPHENE: A REVIEW - Al-mashaal, Asaad K. Edaan (Antis-Publisher, 2024)
Nanotechnology can revolutionize the sensor industry by introducing specific nanomaterials to work as sensing elements. Graphene, a two-dimensional carbon allotrope with exceptional electrical and mechanical properties, has emerged as a promising material for developing high-performance pressure sensors. Graphene-based pressure sensors offer significant advantages over traditional sensors, including high sensitivity, wide dynamic range, fast response time, and flexibility. This paper aims to deliver a review on the fundamental mechanisms underlying graphene-based pressure sensors, which includes piezoresistive, capacitive, and field-effect transistor (FET). Recent advancements in graphene-based pressure sensors have opened up new possibilities in various fields, including healthcare, electronics, and robotics. Here, we will highlight these emerging applications and explore the potential future developments of this technology.